Analisis tegangan pada batang utama mekanisme bukaan payung raksasa - Santoso, G.; Permana, M.S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2017)
Spacious areas as venues for events such as weddings, gatherings, musical performances, bazaars even as parking lots, need to be protected from climate change. Therefore, it is necessary to develop the design of a giant umbrella axle mechanism measuring 12 x 12 meters with a height of 8 meters. This paper describes and stresses the stress analysis on the main bar of the giant umbrella opening mechanism. The result of modeling on the stem is presented in the form of stress contour, factor of safety (FOS), and displacement. The largest working voltage is 2 MPa in the connection area, but this voltage is still low when compared with ASTM A36 rod material structure or equivalent to SS-41 which has a yield strength of 100 MPa. The low voltage von misses are relevant to FOS values that generally reach 100 or more. The largest displacement value is in the center of the stem, which is 0.3 mm. Thus, the modeling results are able to withstand a load of 1 ton.